PROTOTYPE OF LPG GAS LEAKAGE DETECTOR SYSTEM BASED ON FUZZY LOGIC - I Nyoman Gede Muliawan; Suryani Alifah; Arief Marwanto (Journal of Telematics and Informatics, 2020)
LPG is an alternative fuel that is used for daily needs, it is caused not only because of its cheap price but also its easy installation. However, the characteristic of LPG gas which is flammable and heavier than oxygen makes LPG gas leakage is hard to be detected. Based on that problem, a system that is able to detect gas leakage is needed and the system itself has to pass the sensitivity level test to be gas sensor. In this study there are 3 sensors; MQ-2, MQ-5 and MQ-6 gas sensors which are connected to the Arduino Uno microcontroller as it can be used as a feature to classify the condition of the gas by the implementation of the Fuzzy Mamdani method. The output of the system is displayed on an LCD, marked with a buzzer and a fan as gas decoder. The Arduino Uno that was programmed using fuzzy logic was used to control the level of leakage and to give a solution level through the rotation of fan and the buzzer sound. From the test results, the system could determine various conditions of gas leakage with 93% accuracy. From the results of its simulation and test, MQ-5 had higher sensitivity rather than MQ-2 which had the lowest sensitivity toward gas leakage.   Keyword: Leakage, LPG Gas, Fuzzy Logic,